High-Temperature Reorganization Behavior of Single-Crystalline Porous 4H-SiC Thin Foils - Pfusterschmied, Georg; Zellner, Christopher; Leitgeb, Markus; Kirnbauer, Alexander; Schwarz, Sabine; Vengattoor Raghu, Appu; Schmid, Ulrich; Perazzi, Marco; Hahn, Rainer (Materials science forum, 2024)
This work reports on the high-temperature reorganization behavior of single-crystalline porous 4H-silicon carbide (4H-SiC) thin foils. Porous 4H-SiC thin foils are realized via state-of-the-art photoelectrochemical etching in hydrofluoric (HF) acid solution enabling for the first time a released foil with a diameter of 2 inches. Subsequent annealing under inert gas atmosphere and comparison between samples suggests that a temperature of 1500 °C allows for various degrees of compactification across the foil surface, whereas at 1600 °C single crystallinity can be preserved.